Kontroverse um die Alzheimer-Frühdiagnostik – eine literaturbasierte Übersicht über die Vor- und Nachteile - Grässel, Elmar; Lauer, Natascha (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2023)
Background: The continuum of Alzheimer's disease (AD) comprises three stages: the pre-clinical stage (with few to no subjective symptoms), the prodromal stage (measurable mild cognitive impairment) and the final stage of clinically manifest (AD) dementia. Neuropathological correlates in accordance with these stages have been found with varying frequency. The aim of early AD diagnosis is to determine such correlates in these preclinical and prodromal stages and to determine the probability of the manifestation of a later AD dementia. In this regard, the prognostic validity is of vital importance. From the perspective of those affected, the issue of early diagnosis cannot be reduced to AD, although Alzheimer's dementia is by far the most common form of dementia. The aim of this review is to provide a literature-based overview of the advantages and disadvantages of early AD diagnosis in contrast to other types of dementia. Based on this, recommendations will be formulated for the prioritisation of early diagnostic advantages and disadvantages in the patient counselling situation in clinical practice. Methods: Three databases were searched for current reviews addressing the advantages, disadvantages and ethical aspects of early AD diagnosis. The search was limited to current German or English reviews published between January 1, 2018 to November 30, 2022. The systematic search strategy was based on the PICO model and included both a Boolean and a focus-expanding keyword search using previously defined search terms. In addition, snowballing was used as a search strategy. Qualitative synoptic content analysis in accordance with Mayring was used to analyse both advantages and disadvantages. Similar arguments were combined into single statements. The resulting statements were categorized into three main groups: social, individual or clinical aspects. To emphasize the aforementioned aims, arguments were additionally distinguished into “only valid for early AD diagnosis” and ”valid for early diagnosis of all types of dementia“. Results: Overall, seven reviews with suitable content were included. Social aspects of early AD diagnosis comprise the protection of the affected person and the society as well as potential stigmatisation of the affected and their family members. Individual arguments range from the right to a “rational suicide”, including the avoidance of financial and caregiving burdens on family members, to the right not to know the diagnosis. Clinical arguments include, for example, the scientific research context (facilitating the identification of suitable clinical trial participants) and various negative effects of a false positive or false negative early diagnosis. Conclusion: Early diagnosis of AD as well as of other forms of dementia are characterised by numerous advantages and disadvantages of a social, individual and clinical nature. The decision for or against early diagnosis should always be made by weighing the current advantages against the disadvantages in a specific case. In particular, the desires of the person affected, the validity of the diagnostic procedures available and, above all, the availability of effective preventive or therapeutic measures must be taken into account.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Advantages and disadvantages; Alzheimeŕs disease; Biomarkers; Dementia; Early diagnosis; Ethical issues